1997
DOI: 10.1002/art.1780400318
|View full text |Cite
|
Sign up to set email alerts
|

Cr1, CD35 IN synovial fluid from patients with inflammatory joint diseases

Abstract: Objective. To investigate synovial fluid (SF) for the presence of CR1 and to study its relationship to SF leukocytes and to serum levels of soluble CR1 (sCR1) in patients with rheumatic diseases.Methods. Synovial fluids were collected from 35 patients with rheumatoid arthritis (RA) and 26 patients with other inflammatory joint diseases. Total CR1 in the SF and serum were measured with a sandwich enzymelinked immunosorbent assay (ELISA) that recognized both soluble and transmembrane forms of CR1. The characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…We have recently shown that leukocytes release two different forms of CR1 [18]. The first form corresponds to the shedding of the extracellular domain of the transmembrane molecule (sCR1), whereas the second is still bound to membranes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently shown that leukocytes release two different forms of CR1 [18]. The first form corresponds to the shedding of the extracellular domain of the transmembrane molecule (sCR1), whereas the second is still bound to membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The limit of sensitivity was 0.1 ng/mL. The solubility of CR1 in plasma was assessed before and after ultracentrifugation at 200,000 g at 4°C for 1 h. This centrifugation has been shown to pellet vesicle-bound CR1 of erythrocyte-derived and podocyte-derived vesicles [16,17] as well as leukocyte membranes [18].…”
Section: Analysis Of Scr1 In Plasmamentioning
confidence: 99%
See 2 more Smart Citations
“…This important physiological complement inhibitor found in the respiratory tract in soluble form, contrarily to the epithelium-bound complement regulatory proteins membrane cofactor protein, decay-accelerating factor and CD59 [9], may be important to prevent lung injury in several acute and chronic inflammations. The observation that soluble complement receptor type 1 could be measured in bronchoalveolar lavage with a monoclonal antibody known to recognise the C3b/ C4b binding sites suggests that the molecule is functional [46,47]. Whether this complement receptor type 1 release is sufficient to inhibit complement activation in vivo remains to be determined.…”
Section: Discussionmentioning
confidence: 99%